Increased nuchal translucency origins from abnormal lymphatic development and is independent of the presence of a cardiac defect1. (30th October 2015) - Burger, Nicole B.; Bekker, Mireille N.; Kok, Evelien; De Groot, Christianne J. M.; Martin, James F.; Shou, Weinian; Scambler, Peter J.; Lee, Youngsook; Christoffels, Vincent M.; Haak, Monique C.
Abstract: Objective: To assess whether cardiac failure, because of cardiac defects, and abnormal jugular lymphatic development are involved in nuchal edema (NE) – the morphological equivalent of increased nuchal translucency – in various euploid mutant mouse models. Method: Mouse embryos with lymphatic abnormalities and NE ( Ccbe1 − /− ), with cardiac defects and NE ( Fkbp12 −/−, Tbx1 −/−, Chd7 fl/fl ;Mesp1Cre, Jarid2 −/− NE+ ) and with cardiac malformations without NE ( Tbx2 −/−, Pitx2 −/−, Fgf10 −/−, Jarid2 −/− NE− ) were examined. Embryos were analyzed from embryonic day 11.5 to 15.5. Markers for lymphatic vessels, endothelium, smooth muscle cells and nerves were used to study the nuchal region. Hematoxylin–Azophloxine staining was performed to examine cardiac morphology. Results: Mouse embryos with lymphatic abnormalities and NE ( Ccbe1 −/− ) showed no formation of the jugular lymphatic sac but normal cardiac morphology. In mouse embryos with cardiac defects and NE ( Fkbp12 −/−, Tbx1 −/−, Chd7 fl/fl ;Mesp1Cre, Jarid2 −/− NE+ ) enlarged jugular lymphatic sacs or large nuchal cavities within the NE were found. In mouse embryos with a cardiac malformation without NE ( Tbx2 −/−, Pitx2 −/−, Fgf10 −/−, Jarid2 −/− NE− ) normal jugular lymphatic sacs were observed. Conclusion: NE consistently coincides with abnormal jugular lymphatic development in euploid mouse embryos, independent of cardiac anatomy. NE is unlikely to be caused by temporary cardiac failure solely because of a cardiac defect. © 2015 John Wiley & Sons, Ltd. Abstract : What's already known about this topic? Temporary cardiac failure is often referred to as explanation for increased nuchal translucency, despite the absence of direct, conclusive evidence. Abnormal jugular lymphatic development plays an important role in the development of nuchal edema – the morphological equivalent of increased nuchal translucency – in aneuploid embryos. What does this study add? Nuchal edema consistently coincides with abnormal jugular lymphatic development in euploid mouse embryos, irrespective of cardiac morphology. Temporary cardiac failure, because of a cardiac defect, is unlikely to cause nuchal edema.